Inflammation and Immune-Based Scores Predict Prognosis for Patients with Hepatocellular Carcinoma: A Pilot Single-Center Study - Guzel Dirim, Merve; Cifcibasi Ormeci, Asli; Cavus, Bilger; Poyanli, Arzu; Serin, Kursat Rahmi; Akyuz, Filiz; Demir, Kadir; Besisik, Selman Fatih; Kaymakoglu, Sabahattin (Turkish Journal of Gastroenterology, 2025)
Background/Aims: Hepatocellular carcinoma (HCC) ranks as a major contributor to cancer-related deaths. Systemic inflammation plays a pivotal role in HCC development and progression. Thus, we aimed to determine the impact of inflammation- and immune-based scores in predicting the prognosis of HCC. Materials and Methods: In this retrospective study, patients with HCC were enrolled between 2010 and 2020. The purpose of this ret rospective study was to evaluate the impact of various biomarkers, including baseline alpha fetoprotein (AFP) levels, C-reactive protein (CRP) –albu min–l ympho cyte (CALLY) index, neutrophil-to-CRP (N/CRP) ratio, systemic immune-inflammation index (SII), albumin–bili rubin (ALBI) score, neutr ophil -to-l ympho cyte ratio (NLR), and aspartate aminotransferase (AST)-to-alanine aminotransferase (ALT) (AST/ALT) ratio (AAR), on survival, invasion of vascular tracts, metastasis, and treatment responses. Results: A total of 199 patients with complete (n = 44) and non-complete (n = 145) treatment response groups were enrolled in the study. All scores for the non-complete response group were statistically significant (P < .05). The areas under the curves for predicting a non-complete response group were 0.651, 0.649, 0.636, 0.625, 0.613, 0.609, and 0.600 for AFP, CALLY index, AAR, SII, N/CRP ratio, ALBI score, and NLR, respectively. These results are consistent with the assessment of mortality and HCC progression. Conclusion: Our results indicate that these biomarkers could serve as powerful prognostic tools for HCC. Cite this article as: Guzel Dirim M, Cifcibasi Ormeci A, Cavus B, et al. Inflammation and immune-based scores predict prognosis for patients with hepatocellular carcinoma: A pilot single-center study. Turk J Gastroenterol. 2025;36(4):219-228.